An Overview of Reviews on Predictors of Neurorehabilitation in Surgical or Non-Surgical Patients with Brain Tumours - Mattia Gambarin; Tullio Malgrati; Rita Di Censo; Angela Modenese; Giulio Balestro; Gloria Muti; Marta Cappellesso; Cristina Fonte; Valentina Varalta; Ylenia Gallinaro; Monica Pinto; Matilde Carlucci; et al. (Life)
(1) Background. People suffering from brain cancer, regardless of histological tumour characteristics, often experience motor disturbances, cognitive–behavioural difficulty, language impairments, and functional and social limitations. The current treatment approach entails surgery and adjuvant therapy such as chemotherapy and radiotherapy combined with intensive rehabilitation. The primary focus of rehabilitation is usually motor and functional recovery, without specifically addressing the patient’s quality of life. The present systematic review identifies and evaluates the predictors of functional and cognitive rehabilitation outcomes and their influence on quality of life in adult patients with brain cancer. (2) Methods. Three electronic databases (PubMed, Elsevier, Cochrane) were searched for reviews about functional, cognitive, and quality-of-life outcomes in patients with central nervous system tumours, including articles published between January 2018 and May 2024. (3) Results. The search retrieved 399 records, 40 of which were reviewed. Five main areas of predictive factors were identified: diagnosis, therapy, complications, outcomes (in the motor, cognitive, and quality-of-life categories), and tailored rehabilitation. (4) Conclusions. These indicators may inform integrated care pathways for patients with primary central nervous system tumours.